Wiring an [FeFe]-hydrogenase with photosystem I for light-induced hydrogen production. - Lubner, C; Knörzer, P; Silva, P; Vincent, K; Happe, T; Bryant, D; Golbeck, J (2010)
A molecular wire is used to connect two proteins through their physiologically relevant redox cofactors to facilitate direct electron transfer. Photosystem I (PS I) and an [FeFe]-hydrogenase (H(2)ase) serve as the test bed for this new technology. By tethering a photosensitizer with a hydrogen-evolving catalyst, attached by Fe-S coordination bonds between the F(B) iron-sulfur cluster of PS I and the distal iron-sulfur cluster of H(2)ase, we assayed electron transfer between the two components via light-induced hydrogen generation. These hydrogen-producing nanoconstructs self-assemble when the PS I variant, the H(2)ase variant, and the molecular wire are combined.